Carta de Federico Henríquez y Carvajal a Roberto H. Todd - Henríquez y Carvajal, Federico; Todd, Roberto H. (My University, 1939)
Dolencias de Henríquez y sobre la muerte de Betances.
Keywords: Betances y Alacán, Ramón Emeterio, 1827-1898